Climate change in sociology: Still silent or resonating?. (October 2020) - Koehrsen, Jens; Dickel, Sascha; Pfister, Thomas; Rödder, Simone; Böschen, Stefan; Wendt, Björn; Block, Katharina; Henkel, Anna
Since Lever-Tracy's call for stronger sociological engagement with climate change in 2008, the number of climate-related contributions to leading sociological journals has increased. Yet, they still represent a small percentage of contributions overall. Reviewing the 37 articles published in eight top-ranked sociology journals until 2018, the authors of the present article identify five main subfields of research: (a) reflections on the role of the social sciences, (b) politics, (c) economy and consumption, (d) media and public perceptions, and (e) global flows. They conclude that the rise in contributions since 2008 indicates that climate change creates some resonance in the disciplinary core of mainstream sociology but that most sociological climate change research is undertaken and published in inter- and transdisciplinary spaces beyond the boundaries of the discipline. Emphasizing that climate change research can provide important epistemic resources for the discipline, the authors argue that sociology would benefit from being more responsive to it.